Linguistic behaviors of spanish speakers from Guanacaste towards linguistic varieties of spanish from Central Valley speakers - Sancho Ugalde, María (2024)
In this research paper, a study based on linguistic behaviors present in Guanacaste speakers has been performed. The study addresses the linguistic varieties of Spanish in the Central Valle of a student sample from the National University of Costa Rica.The main objective is to analyze the linguistic behaviors of a group of Guanacaste speakers towards the linguistic varieties of Spanish within Central Valle. To accomplish this objective, a five-level Likert scale questionnaire is being proposed as the instrument to collect data on linguistic behaviors from Spanish from Central Valle. Moreover, in the same questionnaire, there have been included three open questions. This qualitative approach is being used to collect valuable information to complement the statistical data. Subsequently, the information obtained from the questionnaires is analyzed using statistical tools such as comparative charts and graphs. The objective would be to determine the linguistic behaviors of Guanacaste students from Chorotega and Omar Dengo’s National University sites. Regarding the results, the majority of the students interviewed (migrated and non-migrated) are aware of the linguistic differences between Guanacaste and Vallecentraleños speakers, linguistic prejudices still persist in the popular belief of some Costa Rican speakers; and finally, related with the linguistic variety under study, the Spanish from the Central Valley, there co-occur accommodation processes or linguistic adaptations, linguistic insecurity, linguistic change (manifested with the phenomenon of migration), attitudes of loyalty and linguistic identity reinforced with attitudes of greater awareness and acceptance of the linguistic and cultural diversity of Costa Rica. It may be concluded that in regard to the perception of the interviewed speakers, the historical division between the varieties of Spanish from Guanacaste and the Central Valley has been kept. However, the study of such linguistic varieties shows a leveling and progressive approach of both linguistic varieties, it is especially notable in those students who have lived abroad. The present study has five sections: the introduction; the theoretical frame; the methodological framework; the qualitative and quantitative analysis of the linguistic behaviors within the areas of the present study (Guanacaste and Central Valley) and finally, conclusions.